Three-dimensional (3D) quantitative evaluation of the morphological changes of the upper anterior alveolar bone after retraction of a maxillary incisor - Hong Liu; Xun Xi; Dongxu Liu (BMC Oral Health, 2023)
Abstract Background The purpose of this study was to assess morphological changes of the upper anterior alveolus after retraction of a maxillary incisor by applying three-dimensional (3D) superimposition of pretreatment (T1) and posttreatment (T2) cone-beam computed tomography (CBCT) data. Methods The study group was comprised of 28 patients with skeletal Class II malocclusion who underwent incisor retraction. CBCT data were acquired before (T1) and after (T2) orthodontic treatment. Labial and palatal alveolar thickness were assessed at the crestal, midroot and apical levels of the retracted incisors. Following three-dimensional (3D) cranial base superimposition, we performed surface modeling and inner remodeling of the labial and palatal alveolar cortex of the maxillary incisors. Paired t-tests were used to compare T0 and T1 bone thickness and volume measurements. Comparisons between labial and palatal surface modeling, inner remodeling and outer surface modeling were performed with paired t-tests in SPSS 20.0 version. Results We observed controlled tipping retraction of the upper incisor. After treatment, the alveolar thickness on the labial sides increased and the palatal alveolar thickness decreased. The labial cortex showed a wider range of modeling area with a larger bending height and a smaller bending angle than the palatal side. The extent of inner remodeling was more prominent than the outer surface on both the labial and palatal sides. Conclusions Adaptive alveolar surface modeling occurred in response to incisor tipping retraction on both the lingual and labial sides although these changes occurred in an uncoordinated manner. Tipping retraction of the maxillary incisors led to a reduction in alveolar volume.